Pengembangan E-Modul Bahasa Inggris Menggunakan Aplikasi Sigil Untuk Mahasiswa Program Studi Teknik Informatika - Mubarok, Tyas Alhim; Arini, Fitri (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This development research aims to produce English e-modules for students of the informatics engineering study program using the Sigil application. The Sigil application is an application for managing and creating digital books in Epub format. This research is research and development with using the ADDIE development model. This model applies five stages, namely Analysis, Design, Develop, Implement, and Evaluate. The data collection method used questionnaire that given to the expert validator and students. The research results show that the English E-module using the Sigil application is valid and reliable for use in the learning process based on expert validation results, with an average score of 3.8 and included in the valid category. Based on student respondents, it shows that 76% of students feel helped in understanding English material using this E-Module. It is easier for students to study material anywhere and anytime.